2015
DOI: 10.4103/0019-5154.160512
|View full text |Cite
|
Sign up to set email alerts
|

Onychomadesis with lichen planus: An under-recognized manifestation

Abstract: Onychomadesis or proximal separation of the nail pate usually results from severe, generalized dermatoses like bullous diseases, hand foot and mouth disease, varicella or severe cutaneous drug reactions. Although lichen planus (LP) produces varied nail manifestations (longitudinal onychorrhexis, onychoschizia, nail pigmentation, pterygium etc.), to the best of our knowledge, onychomadesis as a manifestation of nail LP is not recorded. This report presents two children with onychomadesis arising with generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
4
2
Order By: Relevance
“…Onychomadesis was also uncommonly seen as reported earlier. 19 In contrast to other studies, 9 koilonychia was not observed in any of our patients. Distal nail matrix involvement was seen as lunular changes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Onychomadesis was also uncommonly seen as reported earlier. 19 In contrast to other studies, 9 koilonychia was not observed in any of our patients. Distal nail matrix involvement was seen as lunular changes.…”
Section: Discussioncontrasting
confidence: 99%
“…It was also noted that the percentage of nails showing longitudinal melanonychia was much higher as compared to previous studies because of the predominance of Fitzpatrick skin phototypes IV and V in our study subjects. Onychomadesis was also uncommonly seen as reported earlier 19 . In contrast to other studies, 9 koilonychia was not observed in any of our patients.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Onychomadesis is usually a late manifestation of the hand, foot and mouth disease. This finding was previously described for LP in a case report [17]. We also detected clinically evident onychomadesis in 1 patient.…”
Section: Discussionsupporting
confidence: 90%
“… 4 Infectious diseases, trauma, autoimmune/systemic diseases, and medications may also injure the nail matrix, leading to onychomadesis. 5 , 6 , 7 , 8 Rare cases of idiopathic forms of onychomadesis include familial autosomal dominant inheritance, as well as sporadic genetic mutation. 3 This case illustrates the possible link between CMGT and onychomadesis.…”
Section: Introductionmentioning
confidence: 99%